2020
DOI: 10.1186/s41043-020-0213-1
|View full text |Cite
|
Sign up to set email alerts
|

Complementary feeding practices and nutrient intakes of children aged 6–24 months from Bangladeshi background living in Tower Hamlets, East London: a feasibility study

Abstract: Background: The aim of this study was to assess dietary intakes and complementary feeding practices of children aged 6-24 months who are from Bangladeshi ancestry and living in Tower Hamlets, London, and determine the feasibility of a larger, population-representative study. Methods: Questionnaires for demographic variables and feeding practices, and 24-h dietary recalls were administered to 25 mothers to determine whether it would be feasible to conduct a similar study on a representative sample size of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
(53 reference statements)
1
5
1
Order By: Relevance
“…[ 30 31 32 33 34 ] In a feasibility study conducted among Bangladeshi mothers of children aged 6 to 24 months living in London, there was no significant correlation between ICFI categories and maternal education but this finding may be due to the small sample size. [ 35 ] Similar to our study, a study conducted in Nepal among children aged 6 to 23 months shows that growth monitoring of children was associated with the minimum acceptable diet. [ 36 ] This may be due to the fact that growth monitoring of children provides an opportunity for educating mothers regarding good feeding practices.…”
Section: Discussionsupporting
confidence: 88%
“…[ 30 31 32 33 34 ] In a feasibility study conducted among Bangladeshi mothers of children aged 6 to 24 months living in London, there was no significant correlation between ICFI categories and maternal education but this finding may be due to the small sample size. [ 35 ] Similar to our study, a study conducted in Nepal among children aged 6 to 23 months shows that growth monitoring of children was associated with the minimum acceptable diet. [ 36 ] This may be due to the fact that growth monitoring of children provides an opportunity for educating mothers regarding good feeding practices.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, 18.5% of children between 0-3 months, 40.0% of children between 4-6 months, and 51.9% of children above 6 months faced possible risk of overweight. This high percentage of obesity can be associated to the consumption of high energy dense complementary food [38]. The results in Table 6, presented the percentage distribution of weight for height with regards to the socio-economic status of the care givers (Table 5).…”
Section: Fig 1 Frequency Of Exclusive Breast Feedingmentioning
confidence: 99%
“…A good-quality weaning food has balanced protein and calorie contents, adequate vitamins and minerals, and low fiber with a soft texture. A previous study on complementary feeding in London reported that high protein intake at age 6-24 months is positively associated with the proper growth of the children (Jabri et al, 2020). However, in formulated sample Q2, the protein was 27.70 g in 100 g, which was the highest protein content than the other six market available weaning foods.…”
Section: Discussionmentioning
confidence: 72%